STUDI EVALUASI PENEMPATAN RAMBU DAN MARKA TERHADAP GEOMETRIK JALAN DI KECAMATAN TERNATE BARAT - Muhammad Taufiq Yuda Saputraa; Chairul Anwar (Journal of Science and Engineering, 2021)
About 90% of the information needed to drive is received by the driver visually through the eye. Little information is received by hearing (horns, shock markers) and sense of taste (rough profile/walking markers). The research objective was to evaluate the performance of traffic signs and road markings on several roads in Ternate City.This type of research is a combination of direct field surveys and observations as well as literature (literature) related to the placement of signs and markers in accordance with urban road traffic standards. This research was conducted on Jalan Merdeka and Jalan Ahmad Yani, Ternate City with the consideration that these roads have a fairly high traffic density.The results of the survey and observation of the condition of signs and road markings for Jalan Merdeka and Jalan Ahmad Yani in Ternate City, namely: there are still traffic signs that are not maintained and the condition of the signs is damaged. It is necessary to repair the leaf signs and repainting it. In some direction signs, the shape and size of the writing do not meet the standards of the Minister of the Republic of Indonesia No. 61 of 1993. Recommendations for placing signs and markings on roads with incomplete road equipment are as follows: warning signs for intersections, warning signs for T-junction, crossing signs and placing signs for public facilities.